2018
DOI: 10.1016/j.ajoc.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Is it melanoma-associated retinopathy or drug toxicity? Bilateral cystoid macular edema posing a diagnostic and therapeutic dilemma

Abstract: PurposeTo report the clinical presentation, multimodal imaging, and management of a patient with metastatic melanoma who presented with cystoid macular edema (CME).ObservationsWe report a case of a 71-year-old Caucasian male with metastatic melanoma who presented with bilateral cystoid macular edema after being on treatment with a programmed T cell death ligand 1 inhibitor, MPDL3280, for 1 year. Multimodal imaging techniques, including color fundus photographs, autofluorescence, spectral domain optical coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In recent years, identification of tumor-specific genomic abnormalities has enabled dramatic improvement in the efficacy and tolerability of systemic palliative anticancer therapy. Nevertheless, retinal toxicity has been associated with the recent use of MEK and FRFR inhibitors developed for the treatment of metastatic lung cancer [3,8,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, identification of tumor-specific genomic abnormalities has enabled dramatic improvement in the efficacy and tolerability of systemic palliative anticancer therapy. Nevertheless, retinal toxicity has been associated with the recent use of MEK and FRFR inhibitors developed for the treatment of metastatic lung cancer [3,8,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…A case of npAIR was reported by Kasongole et al showing OCTA void areas in the choroidal vasculature [12]. A case of MAR reported by Patel et al showed perifoveal vessel dropout on the OCTA, both the superficial and deep retinal layers, and perifoveal small vessel dropout but the FAZ was not measured [13]. Both studies were descriptive, did not have a control group and did not obtain objective measurements of the OCTA scans.…”
Section: Discussionmentioning
confidence: 99%
“…OCT findings that have been reported with AIR include the classic "flying saucer" sign with parafoveal attenuation of the outer nuclear layer, external limiting membrane and ellipsoid zone in the presence of subfoveal preservation of these outer retinal elements [3,16]. Other OCT findings include non-leaking intraretinal cystic spaces, retinal pigment epithelium and choriocapillaris atrophy and decreased macular retinal thickness [13], although up to 18% of AIR cases can have normal SD-OCT findings [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other anti-retinal antibodies have been identified in patients with MAR, including 35-kDa Muller glial cell protein, 22 kDa neuronal antigen, 135-kDa, 46-kDa, 94-kDa, 30- kDa, 33-kDa, 35-kDa, 23-kDa, and 30-kDa. 43-64 Since the ERG finding of a preserved a-wave is non-specific and auto-antibodies other than anti-TRPM1 lack specificity, the minimal case-defining features of MAR remain unclear.…”
Section: Cancer-associated Retinopathymentioning
confidence: 99%